An Atmosphere of Libération: The Role of Decolonization in the France-Quebec Rapprochement of the 1960s - Meren, David (The Canadian Historical Review, 2011)
Decolonization's impact was by no means restricted to the Global South. It is impossible to understand developments in the Canada-Quebec-France triangle in the 1960s without referring to the discourse, ideas, and examples of anti-colonial resistance that marked international life after the Second World War. In addition to influencing the postwar development of France and Quebec, the decolonization phenomenon figured prominently in the process of rapprochement that developed between them in the post-1945 period. After discussing the global reach of decolonization, this article examines its impact on the Canada-Quebec-France triangle. Particular attention is paid to its intellectual and political consequences, notably the 'Quebec as colony' metaphor and the reimagining of France as a champion of decolonization. The intersection between these two ideas was crucial to the evolution of the France-Quebec relationship.
Keywords: France; Quebec; Québec; Third World; Tiers-monde; de Gaulle; decolonization; décolonisation; postcolonial

"Commend me the Yak": The Colombo Plan, the Inuit of Ungava, and 'Developing' Canada's North - Meren, David (Histoire sociale / Social History, 2017)
This article engages with the entangled histories of Canadian foreign aid and relations between Indigenous peoples and Canada. Specifically, it traces a proposal in the early 1950s to use the Colombo Plan, the Commonwealth development program in which Canada was a participant, to transfer yaks from India for use in the "development" of the Inuit population in northern Quebec. While the relocation was ultimately never realized, the episode reveals how questions of race and empire, not least the environmental dimension of these, along with the priority accorded to promoting a liberal-capitalist version of "modernization," informed the imaginary underpinning the Canadian state's engagement with Indigenous populations and the Global South. More broadly, the subject matter highlights how the history of Indigenous-settler encounters informed Canadian attitudes regarding development assistance, and vice versa.

Getting Over Tragedy: Some Further Thoughts on Canadian International History - Meren, David (The Canadian Historical Review, 2015)
In addition to engaging with the three commentaries regarding the historiographical essay under discussion, this author’s response considers the future of Canadian international history by posing the following questions: (1) who is Canadian international history for?; (2) what is Canadian international history in service to?; and (3) how should we explore Canadian international history? The answers to these questions emphasize the value of a more inclusive and expansive approach.
Keywords: Canada; empire; histoire internationale; historiographie; historiography; international history; transnational

The Tragedies of Canadian International History - Meren, David (The Canadian Historical Review, 2015)
The early twenty-first century witnessed a shift in Canadian international action, how such action is portrayed, and how Canada’s international history is deployed to understand Canada and its evolution. This shift has contributed to a growing awareness of the intellectual and political significance of Canada’s international history and a heightened awareness of the need for a re-engagement with this history to produce more complex narratives. Demonstrating and encouraging such a re-engagement is the purpose of this historiographical article, which traces the writing of Canadian international history from its origins to a period of crisis in the last three decades of the twentieth century. In so doing, it explores how “empire” and its legacy run through this historiography’s various overlapping currents. Flowing from this discussion, the article highlights three “tragedies” that have marked the historiography and that are reflective of, and linked to, tragedies in the history of Canadian encounters with the world. This is followed by an examination of current trends that are contributing to a renewed, more expansive literature, thereby emphasizing the value and potential of Canadian international history as a means to obtain greater understanding of Canada as a project of rule.
Keywords: Canada; empire; histoire internationale; historiographie; historiography; international history; transnational

LESSONS LEARNED: Settler Colonialism, Development, and the UN Regional Training Centre in Vancouver, 1959-62. - Meren, David (BC Studies, 2020)
IN THE SPRING OF 1959, the UN press service and Canada's Department of External Affairs (DEA) announced that the "rivers, forests, cities and industries of western Canada and northwestern United States [would] serve as a laboratory in economic and social development for a new-type training center." (1) The Regional Training Centre for United Nations Fellows at the University of British Columbia would "enable trainees from underdeveloped countries to study and observe activities in fields such as hydroelectric power, water development, mining, forestry, land management, cooperatives, credit unions, social welfare, and public administration." (2) Press reports explained that the "unique international venture," involving the UN, the Canadian government, and UBC would be located in the Pacific Northwest because "in the past 50 years this area has experienced a most remarkable expansion of population and of economic development." (3) Infused with the postwar optimism associated with Canada's economic progress, British Columbia's resource boom, and international development, the announcement simultaneously highlighted and obscured a history and ongoing reality of settler colonialism and, more broadly, the extent to which Canadian participation in development assistance rested upon a foundation of Indigenous dispossession. This article explores how settler colonialism intersected with the UN's training centre at UBC, which is built on the territory of the Musqueam people. It uncovers what the Centre's origins and activities say about understandings of development after 1945, especially the Canadian dimension of this global history. Specifically, it interrogates development's pedagogical dimension. Situating "technical assistance" and efforts to identify best practices into the literature on imperialism and settler colonialism, it highlights how, notwithstanding progressive motivations, Canadian academic involvement in development efforts rested upon and reified settler colonialism at home and abroad. (4)

Safeguarding Settler Colonialism in Geneva: Canada, Indigenous Rights, and ILO Convention No. 107 on the Protection and Integration of Indigenous Peoples (1957) - Meren, David (The Canadian Historical Review, 2021)
This article explores the intersecting of liberal internationalism and settler colonialism by tracing the Canadian governmental response to the emergence of International Labour Organisation (ilo) Convention 107 (1957) and Recommendation 104 (1957), the first international treaties regarding the rights of Indigenous Peoples in independent states. Drawing upon the archives of the ilo, Canada’s Department of External Affairs and Department of Citizenship and Immigration, notably the latter’s Indian Affairs Branch, the article investigates the convergence of mid-twentieth-century notions of Indigenous rights and the global phenomenon of “development.” It also explores how, amid anti-colonial resistance, decolonization, and an emerging international human rights regime, settler states responded, not least by seeking to blunt if not defeat the ilo initiative. In addition to yielding greater understanding of the origins and emergence of the ilo instruments, this analysis contributes to critical interrogations of Canadian liberal internationalism by revealing how Canadian settler preoccupations were projected abroad and shaped the international system’s evolving treatment of Indigenous Peoples. It also offers a different perspective on Canadian Indian policy by revealing the “global” dimension of an allegedly “domestic” question. Finally, the article highlights a parallel history of Indigenous internationalism speaking back to a world order constructed on Indigenous displacement and dispossession. Le présent article étudie les liens entre l’internationalisme libéral et le colonialisme de peuplement. À cette fin, il relate la réaction du gouvernement canadien devant l’émergence de la Convention 107 (1957) et la Recommandation 104 (1957) de l’Organisation internationale du Travail (oit), premiers traités internationaux portant sur les droits des peuples autochtones dans les États indépendants. À partir des archives de l’ oit, du ministère des Affaires extérieures et du ministère de la Citoyenneté et de l’Immigration du Canada, notamment de sa Division des affaires indiennes, l’article analyse la convergence entre les droits des autochtones, tels qu’ils étaient perçus au milieu du XXe siècle, et le phénomène mondial du « développement ». Il étudie également la manière dont les États colonisateurs, dans un contexte de résistance anticoloniale, de décolonisation et d’émergence d’un régime international des droits de l’homme, ont cherché à amoindrir, voire à faire échouer, l’initiative de l’oit. En plus de permettre de mieux comprendre les origines et l’émergence des instruments de l’oit, cette analyse aide à poser des questions pertinentes au sujet de l’internationalisme libéral canadien, car elle révèle comment les préoccupations des colonisateurs canadiens ont été projetées à l’étranger et ont joué un rôle dans l’évolution du traitement des peuples autochtones par le système international. Elle offre également une perspective différente sur la politique canadienne à l’égard des autochtones en révélant la dimension « mondiale » d’une question prétendument « intérieure ». Enfin, l’article met en lumière une histoire parallèle de l’internationalisme autochtone qui réagit à un ordre mondial construit sur le déplacement et la dépossession des autochtones.

With friends like these entangled nationalisms and the Canada-Quebec-France triangle, 1944-1970 - Meren, David (UBC Press, 2012)

L’évolution du terme « Métis » chez le Conseil national des Autochtones du Canada et l’Alliance laurentienne des Métis et Indiens sans statut entre 1971 et 1982 - Bernard, David (Université de Montréal, 2020)
Between 1876 and 1982, Métis were excluded from federal Indian policy, as they were not recognized as indigenous owing to the discriminatory and assimilationist clauses within the Indian Act. However, numerous spaces emerged for the recognition of the indigenous nature of the rights and identities of Métis and non-status Indians (MNSI) amid the creation of the Native Council of Canada in 1971 and the repatriation of the Canadian constitution in 1982. Among these were the creation of MNSI representative organizations across the country, the funding of historical and legal research for land claims, and lastly, the recognition of Métis rights as an Aboriginal people within the constitution. Within the scope of these spaces and the pressing context of land claims and constitutional repatriation, the NCC and the Laurentian Alliance of Metis and non-status Indians (LAMNSI) highlighted different ideas and definitions on the rights and identities of MNSI people in Canada in order to be recognized by the state. For this reason, the CNAC valued an ethno-national concept of Métis that was centered around the Red River community. Consequently, LAMNSI argued that there was no such thing as a Métis Nation in Quebec or in eastern Canada. Instead, LAMNSI affirmed that its members belonged to the historical, cultural and familial realities of the First Nations.
Keywords: Alliance laurentienne des Métis et Indiens sans statut; Autochtone; Conseil national des Autochtones du Canada; Constitution; History - Canadian / Histoire - Canadienne (UMI : 0334); Identity; Identité; Indiens sans statut; Indigenous; Land claims; Laurentian Alliance of Metis and non-status Indians; Métis; Native Council of Canada; Non-status Indians; Revendications territoriales

Conclusion : race and the future of Canadian international history - Meren, David (Dominion of race: rethinking Canada's international history, 2017)
How has race shaped Canada's international encounters and its role in the world? How have the actions of politicians, diplomats, citizens, and non-governmental organizations reflected and reinforced racial power structures in Canada? In this book, leading scholars in Canadian international relations grapple with these complex questions, destabilizing conventional understandings of Canada in the world. Dominion of Race exposes how race thinking--normalizing racial differences and perpetuating them through words and actions that legitimize a discriminatory system of beliefs--has informed priorities and policies, positioned Canada in the international community, and contributed to a global order rooted in racial beliefs. Four themes develop throughout the volume: the relationship between empire, identity, and liberal internationalism; the tensions between individual, structure, theory, and practice; the mutual constitution of domestic and international spheres; and the notion of marginalized terrain and space. While the contributors reconsider familiar topics, including the Paris Peace Conference and Canada's involvement with the United Nations, they also enlarge the scope of Canada's international history by subject, geography, and methodology. By demonstrating that race is a fundamental component of Canada and its international history, this book calls for reengagement with the histories of those marginalized in, or excluded from, the historical record.

Crisis of the nation : race and culture in the Canada-Quebec-France triangle of the 1960s - Meren, David (Dominion of race: rethinking Canada's international history, 2017)
How has race shaped Canada's international encounters and its role in the world? How have the actions of politicians, diplomats, citizens, and non-governmental organizations reflected and reinforced racial power structures in Canada? In this book, leading scholars in Canadian international relations grapple with these complex questions, destabilizing conventional understandings of Canada in the world. Dominion of Race exposes how race thinking--normalizing racial differences and perpetuating them through words and actions that legitimize a discriminatory system of beliefs--has informed priorities and policies, positioned Canada in the international community, and contributed to a global order rooted in racial beliefs. Four themes develop throughout the volume: the relationship between empire, identity, and liberal internationalism; the tensions between individual, structure, theory, and practice; the mutual constitution of domestic and international spheres; and the notion of marginalized terrain and space. While the contributors reconsider familiar topics, including the Paris Peace Conference and Canada's involvement with the United Nations, they also enlarge the scope of Canada's international history by subject, geography, and methodology. By demonstrating that race is a fundamental component of Canada and its international history, this book calls for reengagement with the histories of those marginalized in, or excluded from, the historical record.

Rights of Passage: The Intersecting of Environmentalism, Arctic Sovereignty, and the Law of the Sea, 1968–82 - Meren, David; Plumptre, Bora (Journal of Canadian Studies/Revue d'études canadiennes, 2013)
This essay brings environmental and diplomatic history into conversation in order to examine the Trudeau government’s response to the 1969–70 voyages of the oil tanker Manhattan through the Northwest Passage. By passing the Arctic Waters Pollution Prevention Act and extending Canada’s territorial sea to 12 miles, Ottawa successfully instrumentalized the heightened environmental concern of the period in order to press Canadian claims to sovereignty in the Arctic. The essay demonstrates that this custodial approach was consistent with the functionalist tradition in Canadian liberal internationalism. More broadly, it reveals the promise of re-examining Canadian international history through the prism of environmental history.

Les influences transnationales sur la nationalisation de l’électricité au Québec (1934-1963) - Giguère, William (Université de Montréal, 2015)
Ce mémoire de maîtrise analyse les influences transnationales qui ont mené à la nationalisation de l’électricité au Québec. En contraste avec les précédentes études sur Hydro-Québec voulant que les incitatifs locaux fussent la source exclusive de la nationalisation de l’électricité au Québec, cette recherche vient démontrer que les idées transnationales ont été tout aussi influentes. Tout au long du récit, on voit que la conjoncture politico-économique de refonte du libéralisme économique classique vers une version plus keynésienne de l’économie occidentale a été un stimulant de première importance pour la nationalisation de l’électricité au Québec. Dans le premier chapitre sont détaillées les nationalisations d’électricité de l’Ontario, de la Vallée du Tennessee et de la France, ainsi que les relations qu’elles ont eues entre elles et avec le Québec. Dans un second temps, il est démontré que l’étatisation de l’électricité en Ontario au début du XXe siècle et celle de la Vallée du Tennessee durant la crise économique des années 1930 ont été des incitatifs majeurs pour le projet menant à la nationalisation de la Montreal Light Heat & Power en 1944. Enfin, dans le troisième chapitre, ce sont les influences venant des nationalisations d’électricité étasunienne, ontarienne et française sur la nationalisation de l’ensemble des compagnies d’électricité québécoises de 1963 qui sont analysées.
Keywords: EDF; Electricity; History - Canadian / Histoire - Canadienne (UMI : 0334); Hydro-Québec; Keynesianism; Keynésianisme; Nationalisation; Nationalization; Ontario Hydro; Planification; Planning; Québec; Tennessee Valley Authority; Transnational; Électricité

L’Association des Indiens du Québec (1965-1977) et le militantisme autochtone dans le Québec des années 1960-1970 - Turcotte, Yanick (Université de Montréal, 2018)
Formée en 1965, l’Association des Indiens du Québec (AIQ) fut la première organisation panindienne qui souhaitait rassembler au sein d’un même regroupement toutes les communautés autochtones au Québec. Largement négligée dans l’historiographie, elle participa pourtant activement aux débats politiques qui entouraient les enjeux autochtones dans les années 1960 et 1970. Ce mémoire se propose d’explorer en deux temps l’histoire de l’Association. D’abord, en étudiant chronologiquement son histoire politique, notre objectif est d’éclairer le rôle qu’elle jouait dans le jeu politique canadien et québécois. En s’y taillant graduellement un espace discursif, l’Association des Indiens du Québec devint l’acteur prédominant qui parlait au nom des populations « indiennes » au Québec et qui soulevait des sujets peu discutés auparavant dans la sphère politique québécoise. Ensuite, ce mémoire aborde, thématiquement, l’histoire sociale de l’Association en explorant la question identitaire et ses impacts administratifs et sociaux. Tout au long de son existence, l’AIQ se définissait comme la représentante « des Indiens du Québec », identité qui, bien qu’ancrée dans une définition légale inscrite dans la Loi sur les Indiens, était une manifestation d’une volonté politique d’unir des communautés disparates qui partageaient, selon elle, une histoire et des problèmes communs. Ce mémoire, en continuité avec les développements récents en histoire autochtone et en histoire du Québec, se propose de sonder une organisation et une période qui n’ont pas été étudiées, mais qui demeurent formatrices dans l’histoire du militantisme autochtone contemporain.
Keywords: "Indian" identity; History - Canadian / Histoire - Canadienne (UMI : 0334); Identité; Indigenous activism; Indigenous organizations; Indigenous-Québécois relations; Land claims; Militantisme autochtone; Organisation autochtone; Pan-Indianism; Panindianisme; Relations Autochtones-Québécois; Revendications territoriales

Le gouvernement du Québec, les relations internationales et l'environnement économique international (1973-1994) - Hamel-Perron, Hugo (Université de Montréal, 2016)
L'objectif de ce mémoire est de jeter les bases d'un nouveau récit historique portant sur les relations internationales du Québec, en rupture partielle avec le récit traditionnel, essentiellement issu des écrits provenant de la science politique, qui décrit l'activité internationale du gouvernement québécois en cherchant dans les particularités de l'histoire québécoise elle-même les forces de changement. Ce faisant, nous tentons plutôt de montrer que l'histoire des relations internationales du Québec est inexorablement enchâssée dans l'histoire canadienne, dans l'histoire nord-américaine et surtout dans l'histoire du capitalisme et du néolibéralisme. Depuis le début de son existence en tant qu'entité politique moderne, le gouvernement québécois entretient des liens avec des gouvernements étrangers, l'intensité de ceux-ci étant function des grandes transformations affectant le système capitaliste international au grand complet. Vers la fin de la période 1867-1973, la politique internationale du gouvernement québécois est institutionnalisée politiquement et juridiquement grâce à la formulation de la doctrine Gérin-Lajoie, qui s'appuie sur les dispositions constitutionnelles propres au Canada pour élaborer la politique internationale québécoise. Dans la période 1973-1981, les relations internationales du Québec se focalisent davantage sur des questions économiques, telles que la quête de capitaux étrangers et la projection d'une image de marque positive sur les marchés étrangers. Puis, dans la période 1981-1994, l'activité internationale du Québec est marquée par le virage néolibéral qui affecte tous les gouvernements capitalistes dans le monde. Ainsi, l'appareil diplomatique du Québec est de plus en plus perçu comme un outil de promotion des exportations des entreprises québécoises et d'adaptation à l'augmentation de l'interdépendance économique, et de moins en moins comme un réseau de contacts politiques et culturels. Afin de faire cette démonstration, nous puisons essentiellement dans deux types de sources primaires : d'une part, des sources gouvernementales, dont les rapports annuels des différents ministères associés aux relations internationales du Québec et du Canada au fil de la période et les livres blancs de politique internationale qu'ils ont publié, et d'autre part, des publications issues du milieu des affaires, dont la revue Les Affaires, excellent baromètre de la mentalité dominante de la classe entrepreneuriale du Québec et du Canada francophone.
Keywords: ALÉ; ALÉNA; Canada; Capitalism; Capitalisme; FTA; FTAA; Free trade; History - Canadian / Histoire - Canadienne (UMI : 0334); International relations; Libre-échange; Neoliberalism; Néolibéralisme; Quebec; Québec; Relations internationales

Dominion of race: rethinking Canada's international history - McKenzie, Francine; Meren, David; Madokoro, Laura (UBC Press, 2017)
How has race shaped Canada's international encounters and its role in the world? How have the actions of politicians, diplomats, citizens, and non-governmental organizations reflected and reinforced racial power structures in Canada? In this book, leading scholars in Canadian international relations grapple with these complex questions, destabilizing conventional understandings of Canada in the world. Dominion of Race exposes how race thinking--normalizing racial differences and perpetuating them through words and actions that legitimize a discriminatory system of beliefs--has informed priorities and policies, positioned Canada in the international community, and contributed to a global order rooted in racial beliefs. Four themes develop throughout the volume: the relationship between empire, identity, and liberal internationalism; the tensions between individual, structure, theory, and practice; the mutual constitution of domestic and international spheres; and the notion of marginalized terrain and space. While the contributors reconsider familiar topics, including the Paris Peace Conference and Canada's involvement with the United Nations, they also enlarge the scope of Canada's international history by subject, geography, and methodology. By demonstrating that race is a fundamental component of Canada and its international history, this book calls for reengagement with the histories of those marginalized in, or excluded from, the historical record.

Construire la guerre totale par l'image au Canada (1914-1918) : acceptation différenciée d'un discours de guerre « totalisé » - Dubé, Alexandre (Université de Montréal, 2017)
Ranging from contemporaries to observers of the XX and XIX centuries, the First World War is a part of human history difficult to portray that many have described as a “total war”. This concept, which is often employed as a synonym for a war of extreme intensity, is generally perceived from a material angle. In other words, it involves an all-out mobilisation of human, financial, and material resources. As part of this research, I focus on the intention to completely destroy the enemy at the risk of destroying oneself in the process. After all, why would actors think it logical to risk self-destruction in the war? Above all, this struggle needs to be perceived as logical, which would make it necessary for their own survival; it could even be perceived as desirable because it presages a better future. For this reason, the study of the Canadian case is quite instructive because this British dominion, without objectively being threatened with destruction, has participated in a war effort in a way comparable to Western European states. Hence, understanding the concept of Canadian “total war” of 1914-1918 can enable us to better understand total war efforts of other countries and other conflicts. In this dissertation, I propose a twofold discursive analysis based on images of war—drawings, caricatures, and posters. In the first part, a new “vocabulary” of total war common to the Allies and comprised of myths, images and key words geared to the articulation of a common war language is created in the in the international arena. In the second part, Canada adopts this language, albeit in a differentiated form, for political, ethno-linguistic cultural, and many other reasons. The dynamic of identity creation is borrowed from abroad (“Us”, the Allies against “Them”, the enemies of civilisation) and is transposed to the national level, culminating during the elections of December 1917. By observing how Canada reacted to the resulting stress of the total war effort of the Allies, it is possible to develop an alternative observation of political and social struggles of the Dominion at war that runs counter to traditional historiographies. I propose a portrait of Canadian society where identity, ideas, gender, and a sense of belonging to the Canadian community do not depend on one’s ethnicity, but rather on whether or not one supports the objectives of the total war put forth by the Allies. In brief, the sense of belonging to an international community of ideas at war—the Allies—, according to this analysis, is the guiding principle for nationalist Canadian actors.
Keywords: Affiches de guerre; Canada; Canada anglais; Canada français; Canadian imperialism; English Canada; First World War; French Canada; Grande Guerre; Great War; Guerre totale; History - Military / Histoire - Militaire (UMI : 0722); Identity; Identité; Impérialisme canadien; Première Guerre mondiale; Propaganda; Propagande; Total war; War posters

La vague des nationalismes : Jules Léger et l'échec de la diplomatie discrète - Meren, David (Mission Paris: les ambassadeurs du Canada en France et le triangle Ottawa-Québec-Paris, 2012)

Intervening with abandon: The Conquest's Legacy in the Canada-Quebec-France Triangle of the 1960s - Meren, David (Remembering 1759 the conquest of Canada in historical memory, 2012)